Enantiocomplementary C–H Bond Hydroxylation Combining Photo‐Catalysis and Whole‐Cell Biocatalysis in a One‐Pot Cascade Process. Issue 7 (12th February 2020) - Peng, Yongzhen; Li, Danyang; Fan, Jiajie; Xu, Weihua; Xu, Jian; Yu, Huilei; Lin, Xianfu; Wu, Qi
Abstract : Enantiocomplementary hydroxylation of alkyl aromatics through a one‐pot photo‐biocatalytic cascade reaction is described. The photoredox process is implemented in aqueous phase with O2 as oxidant and the subsequent ( R )‐ or ( S )‐selective bioreduction is performed by whole cell system without the addition of the expensive cofactor (NADPH). This mild, operationally simple protocol transforms a wide variety of readily available aromatic compounds into valuable chiral alcohols with high yield (up to 90 %) and stereoselectivity (up to 99 %), thereby displaying important potentials in organic synthesis. Abstract : An alternative one‐pot cascade protocol combining photo‐catalysis and whole‐cell biocatalysis for the production of enantiocomplementary alcohols was developed.